METHODS FOR TREATMENT OF REFRACTORY GENERALIZED MYASTHENIA GRAVIS - WANG JING JING; CAMILLE BEDROSIAN; FANNY O'BRIEN (2024)
To provide methods of treating refractory generalized myasthenia gravis.SOLUTION: The disclosure provides methods of treating myasthenia gravis (MG) in a subject in need thereof by administering to the subject a substance that specifically binds complement component 5 (C5). In certain embodiments, the substance that specifically binds C5 is a binding protein, such as an anti-C5 antibody.SELECTED DRAWING: None 【課題】難治性全身型重症筋無力症を処置する方法を提供する。【解決手段】本開示は、補体成分５（Ｃ５）に特異的に結合する物質を被験体に投与することにより、それを必要とする被験体において重症筋無力症（ＭＧ）を処置する方法を提供する。特定の実施態様において、Ｃ５に特異的に結合する物質は、抗Ｃ５抗体のような結合タンパク質である。【選択図】なし